(untitled) (Faculty of Education Scientific Journal, 2024)
Abstract The research aimed to identify the reality of the practice of administrative bullying behavior on employees of Sirte University, and the most common forms. The research population consisted of university employees, numbering (1579) male and female employees. The sample size was determined according to Joel Morgan to determine the sample, as the number of sample members reached (315). Single, and to achieve the goal of the research, the data collection tool represented by the questionnaire was developed, which in its final form consisted of 25 statements that represented behaviors of administrative bullying practiced on the bullied. The research concluded that there are behaviors of administrative bullying practiced against employees at Sirte University at a high rate, and others occur at a moderate rate. The research also showed that there are statistically significant differences according to the gender variable in favor of females in exposure to administrative bullying behavior. The research presented a set of recommendations that aim to Confronting the phenomenon of administrative bullying towards employees at Sirte University and working to limit its practice and spread.